Physical therapy of spasticity for correction of spatiotemporal impairments of gait in children with cerebral palsy - Yun Byoung Yul; О. B. Nekhanevych (Zaporozhye State Medical University, 2021)
The aim of the work is to increase the effectiveness of physical therapy of motor impairments in children with spastic form of cerebral palsy by applying a program of therapeutic training on the device developed for rehabilitation of people with musculoskeletal disorders. Materials and methods. 30 children aged 6 to 11 years with cerebral palsy-associated spastic diplegia were included in the study. Patients were divided into 2 groups. In addition to the standard rehabilitation program, all patients were prescribed therapeutic gait training using a device for rehabilitation of people with musculoskeletal disorders: group I (n = 14) - according to the dynamic method; group II (n = 16) - by static method. The spatiotemporal characteristics of gait, activity daily indicators, the level of spasticity of lower extremity muscles, functional characteristics of gait, and the methods of mathematical statistics were studied. Results. The implementation of the elaborated program of therapeutic exercises using a device for rehabilitation of people with musculoskeletal disorders had a positive effect on the level of muscle spasticity of the lower extremity, stride length, walking speed, general endurance. It also improved balance and reduced the risk of falling in children with cerebral palsy. Conclusions. The application of the elaborated therapeutic program had a positive effect on the spatiotemporal characteristics of walking, balance and functional condition of children with cerebral palsy, as well as reduced the level of spasticity. The increase in the stride length occurs during the first 4 weeks of training, and functional condition indicators showed the greatest dynamics only after 6 weeks of training. The elaboration of the rehabilitation device with the ability to move and apply the technique of exercising with partially unstable pelvic support by the abductor-lift moving along the vertical axis, positively affected the balance and reduced the risk of falling.